Personality (at Intrapsychic and Interpersonal Level) Associated With Quality of Life in Patients With Cancer (Lung and Colon). (26th November 2019) - Giulietti, Maria Velia; Vespa, Anna; Ottaviani, Marica; Berardi, Rossana; Balercia, Giancarlo; Arnaldi, Giorgio; Gattafoni, Pisana; Fabbietti, Paolo; Rosa, Mirko Di; Spatuzzi, Roberta
The objective of this study was to determine the association of quality of life (QoL) and intrapsychic and interpersonal behaviors (Structural Analysis of Social Behavior [SASB]) of patients with cancer (lung: n = 88; age 62.8 ± 10.1; colon: n = 56; age 60.1 ± 11.4). Personality described by SASB clusters (Cls): SASB-Questionnaire; QoL tests: FACT_G and QLQ-C30. Patients with lung cancer (n = 88; age 62.8 ± 10.1) and colon cancer (n = 56; age 60.1 ± 11.4; all stages of severity). Multiple regression analyses. Multiple linear regression: dependent variable: FACT_G; covariates: physical functioning, cognitive functioning, SASB-Cl3-50°, SASB-Cl6-50°. Analysis of variance and t test confirm validity of the model ( P < .001). SASB-Cl3 with FACT_G ( P = .034); SASB-Cl6 with FACT_G ( P = .002); age with FACT_G ( P = .018); physical functioning with FACT_G ( P < .001); cognitive functioning with FACT_G ( P < .001). Personality traits such as self-critical and oppressive behaviors, low capacity for self-esteem, physical and cognitive functioning, and age (a higher age determines a better QoL) strongly determine QoL in patients with lung and colon cancer. This may suggest areas of therapeutic intervention.